IJPS 2022
DOI: 10.36468/pharmaceutical-sciences.947
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Biological and Traditional Claims on Averrhoa bilimbi: An Overview

Abstract: Garg et al.: Recent updates on Averrhoa bilimbi: An approachAverrhoa bilimbi is primarily utilized in traditional medicine to cure blood pressure, high levels of sugar in the blood and many infectious diseases. The key objective of the current review is to assemble and establish literature based on traditional claims and relate those with up-to-date pharmacological results on the use of Averrhoa bilimbi for managing diverse diseases. Literature was collected, systematically assessed, understood and discoursed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is necessary to consider alternative therapies for treating hypertension using natural products [8]. One of the natural products that have the potential to be used for treating hypertension is bilimbi [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to consider alternative therapies for treating hypertension using natural products [8]. One of the natural products that have the potential to be used for treating hypertension is bilimbi [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, bilimbi was known as "Belimbing Wuluh". Traditionally bilimbi has been used to treat several diseases [9,10]. Research related to the use of water stew from bilimbi to reduce hypertension has been reported before [11].…”
Section: Introductionmentioning
confidence: 99%